Emigration Chests in Ankara, Turkey: Tracing Spatial Trajectories of Tatar Community - Akış, Tonguç; Akış, Tonguç (SAGE Publications Inc., 2022)
During migration, whether due to war, political conflict, or poverty, immigrants of turmoil carry their limited personal belongings, family items, and supportive objects in their luggage, bags, and, in some cases, chests to their new homes. Throughout this displacement, chests of migration are necessary and valuable witnesses via their materiality and they wait in their specific corners of houses dare to be contemplated. After the demanding journey, some immigrants continue to use both the chest itself and its contents at their new house in the target locations. In addition, used chests and their contents link immigrants to the journey and to the former location. The immigrants often choose to organize, decorate, and arrange their homes and rooms according to these chests and the items within. This rich mutual relationship between chest, immigrant, and house allows for multidimensional readings considering the spatial trajectories and narratives of migration. Moreover, the trialectic relationships of chest, immigrant, and their space within generate the arguments on the production of space in particular. In this paper, decoding of recent in-depth interviews, documentation of chest locations on each space, and revealing archival material of immigrant families in Ankara, Turkey, are systematized to illustrate the journey of emigration together with the particularities of chest keepers' attitudes and feelings. Additionally, inscriptions, contents, types, and paths of chest are unlocked on private and communal spaces of the Tatar community. This paper aims to uncover those implanted, profound, and engrained interactions on space of immigrant during expedition of chest.
Keywords: Spatial trajectory; Emigration chests; Community development; Production of space; Everyday life